Nursing research using life history: qualitative designs and methods in nursing - De Chesnay, Mary (Qualitative designs and methods in nursing, 2014)
Life history is a qualitative research method used to understand how people successfully cope with illness, traumatic events, or other afflictions. Individual histories are told to the researcher, who in turn frames the story within the cultural context in which the person lives. In this book, experienced scholars in qualitative life history research discuss the theoretical rationale for using this design, describe its components, and delineate a practical plan to conduct studies, including a focus on appropriate methods, ethical considerations, and potential pitfalls. Examples from published nursing research with author commentary help to support new researchers in making decisions and facing challenges. This concise, ""how to"" guide to conducting ethnography research is part of seven-book nursing series, Qualitative Designs and Methods, that focuses on qualitative methodologies. The series will be of direct aid to novice nurse researchers and specialists seeking to develop or enhance their competency in a particular design, graduate educators and students in qualitative research courses, research sections in larger hospitals, and in-service educators and students. The book describes traditional and focused life history, phases of research, and methodology from sample and setting to dissemination and follow-up. Case studies follow a template that includes a description of the study, data collection and analysis, and dissemination. The book also discusses techniques whereby researchers can ensure high standards of rigor. With a focus on practical problem solving throughout, the book will be of value to novice and experienced nurse researchers, graduate teachers and students, in-service educators and students, and nursing research staff at health care institutions. Key Features: Includes examples of state-of-the-art life history nursing research with content analysisDescribes types of life history, phases of research, and methodologyProvides case studies, including description, data collection and analysis, and disseminationWritten by published scholars of qualitative life history